Xerophyte Caralluma stalagmifera var. longipetala (Asclepiadaceae): a new record to the flora of Karnataka, India - M.R. Naik; Y.L. Krishnamurthy (Journal of Threatened Taxa, 2012)
Caralluma stalagmifera C.E.C. Fisch. var. longipetala Karupp. & Pull., is reported for the first time from the state of Karnataka, with descriptive notes and illustrations..